Evaluating the Use of Video Modeling With Voiceover Instructions to Train Therapists to Deliver Caregiver Training Through Telehealth. Issue 2 (March 2023) - Preas, Elizabeth; Carroll, Regina A.; Van Den Elzen, Gabriella; Halbur, Mary; Harper, Megan
Caregiver training is an important component of behavioral intervention; however, many barriers exist for in-person training. Alternatively, behavioral therapists may use telehealth as a service delivery method. To effectively train caregivers through telehealth, therapists should receive explicit training, but there has been limited research on effective methods for teaching this skill. The purpose of the current study was to evaluate video modeling with voice-over instruction (VMVO) to train therapists to implement 11 component skills of caregiver training through telehealth to teach confederate caregivers to implement a guided compliance procedure. We measured the therapist's implementation of the component skills during a scripted role-play before and after video-model training within a multiple baseline design across participants. We also conducted maintenance and generalization probes to a novel skill. All seven therapists learned the skill, but three therapists required a feedback component in addition to the VMVO. The results suggest that VMVO may be an efficient and effective method for training therapists to conduct caregiver training via telehealth. Furthermore, results indicate that component skill analyses may be valuable to monitor skills that require remediation.